Relationship between incidence and severity of peanut smut and its regional distribution in the main growing region of Argentina - Paredes, Juan Andrés; Edwards Molina, Juan Pablo; Cazon, Luis Ignacio; Asinari, Florencia; Monguillot, Joaquín Humberto; Morichetti, Sergio A.; Rago, Alejandro Mario; Torres, Adriana M. (Springer, 2021)
Peanut smut, caused by the soil-borne pathogen Thecaphora frezii, has increased in incidence in the main Argentinian peanut-growing regions. Smut-affected pod transform the kernel into a mass of teliospores, which survive in the soil for long time. This study is the first large-scale (regional) survey to determine the occurrence and distribution of peanut smut in the main peanut-growing area of Argentina. Surveys were conducted in Córdoba province, in randomly selected commercial peanut fields (n = 217) grown from 2015 to 2020. A five-score severity scale has been used to quantify the severity of smut on pods (0 = healthy kernels and 4 = totally smutted kernels), and a disease severity index (DSI) was calculated. Pods with severity scores of 3 and 4 are rejected by the industry and produce a high volume of spores that spread among fields increasing the inoculum in the soil. Those pods were classified as severely damaged pods (SDP). The relative frequency of smut classes during the years was evaluated and the relationships between the yearly incidence and DSI were determined. The mean of the incidence was variable (never zero) across the years and increased from 1.66% in 2015 to 11.47% in 2020. More than 80% of the affected pods belonged to SDP category. The variable SDP, a more time and cost-effective method for quantifying peanut smut, best explained the variation in DSI values. Our results suggest that that visual estimates of incidence and SDP should be useful for disease monitoring, screening genotypes, or treatment comparisons in smut management experiments. Our survey data provided an update in the knowledge of T. frezii distribution over the peanut-growing area of Argentina.